2021
DOI: 10.1080/10715762.2021.2024816
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1287-5p promotes ferroptosis of osteosarcoma cells through inhibiting GPX4

Abstract: Figure S1. Overexpression of miR-1287-5p induces ferroptosis and inhibition of human osteosarcoma cells. (A) Relative LPO and MDA levels at 96 h after the miR-1287-5p mimic (100 nmol/L) transfection (n=6). (B-C) The releases of 5-HETE and 15-HETE to the medium from the miR-1287-5p mimic (100 nmol/L)transfected cell (n=6). (D) Intracellular GSH levels (n=6). (E) Quantification of cystine uptake levels (n=6). (F) Relative protein level of GPX4 in human osteosarcoma cell lines treated with the miR-1287-5p mimic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…As research progresses, the implications of ferroptosis in the development, progression, and multi-drug resistance of osteosarcoma are becoming better known, providing new avenues for treating osteosarcoma and overcoming chemoresistance (74). For illustration, it was found that MicroRNA-1287-5p promotes ferroptosis in osteosarcoma cells by inhibiting GPX4, but its expression is downregulated in human osteosarcoma relative to controls (78). These results suggest that ferroptosis may be regulated by different genes or non-coding RNAs in osteosarcoma, but the expression of these regulators differs in osteosarcoma and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As research progresses, the implications of ferroptosis in the development, progression, and multi-drug resistance of osteosarcoma are becoming better known, providing new avenues for treating osteosarcoma and overcoming chemoresistance (74). For illustration, it was found that MicroRNA-1287-5p promotes ferroptosis in osteosarcoma cells by inhibiting GPX4, but its expression is downregulated in human osteosarcoma relative to controls (78). These results suggest that ferroptosis may be regulated by different genes or non-coding RNAs in osteosarcoma, but the expression of these regulators differs in osteosarcoma and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…KDM4A expression was significantly upregulated in OS tumor tissues relative to normal tissues, while KDM4A knockdown promoted ferroptosis in osteosarcoma cells, limited pulmonary metastasis of osteosarcoma, and could act synergistically with cisplatin ( 77 ). MicroRNA-1287-5p promotes ferroptosis in osteosarcoma cells by inhibiting GPX4, but its expression is downregulated in human osteosarcoma relative to controls ( 78 ). These results suggest that ferroptosis may be regulated by different genes or non-coding RNAs in osteosarcoma, but the expression of these regulators differs in osteosarcoma and normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 165 Recently, it was also found that miRNA-1287-5p could inhibit the progression of osteosarcoma cells by inhibiting GPX4 to promote ferroptosis in osteosarcoma cells. 166 However, there are few literatures about the mechanism of miRNAs regulating ferroptosis in osteosarcoma, and a lot of research is needed to make up for this deficiency in the future.…”
Section: The Role and Mechanism Of Mirnas In The Development Of Osteo...mentioning
confidence: 99%
“…Thus, microRNAs targeting Keap1 and activating Nrf2 can be considered as anti-ferroptotic [ 6 ]. Pro-ferroptotic microRNAs directly target the SLC7A11/GPX4 system and facilitate lipid peroxidation, which provokes ferroptosis [ [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Besides directly targeting GPX4, its expression was shown to be regulated by HSPA5, a target gene of ATF4.…”
Section: Introductionmentioning
confidence: 99%